Development and Standardization of a Lip Reading Test in Hindi Language to Detect Pseudo-Hypacusis - Sadia Sehar (Journal of All India Institute of Speech and Hearing, 1970)
In its most simplest terms 'non-organic hearing loss means an exaggerated elevation of auditory thresholds'. Martin(1981), has defined the term as 'an apparent loss of hearing sensitivity without organic pathology,  to explain the loss or with insufficient pathology to explain the extent of loss'. Many tests have been developed to aid in the diagnosis of functional or non-organic hearing loss. Some of these tests are: Stenger test, Lombard test, Doerfler Stewart test, etc. (Alberti, 1970). Non-organic hearing loss cases can be identified by the use of a standardized test for lip reading ability  (Utley,1940), often with excellent results. Falconer (1960) also found that, as these patients emphasize their ability to lip read, they would usually submit to a' lip reading test'.